Ceramic coating aerogel heat insulation pad and preparation method thereof
By adding ceramic coating and chemically depositing ceramic fibers to the silicone aerogel insulation pad, grafting hollow microbeads to form a dense and high-temperature resistant structure, the problem of structural collapse and thermal insulation performance of silicone insulation pad at high temperature is solved. , achieving higher thermal insulation, impact resistance and flame retardant properties.
Patent Information
- Application Number
- CN202411350702.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-20
AI Technical Summary
The existing silicone aerogel insulation pads have problems such as structural collapse, reduced thermal insulation performance, low impact strength and poor sealing at high temperatures, making it difficult to have both thermal insulation, flame retardant, combustion burst pressure impact and insulation safety performance.
Using ceramic-coated aerogel insulation pad, a dense and high-temperature resistant structure is formed by combining vapor-phase silica, iron hydroxide sol, ceramic powder, chemically deposited ceramic fibers with hollow microbeads and chopped glass fibers. , improve the strength and stability of the insulation pad, and form a closed-cell layer through the chemical deposition process to reduce the thermal conductivity.
Keep the thermal insulation performance at high temperatures without failure, improving the structural stability and thermal insulation effect of the insulation pad, reducing the thermal conductivity, and enhancing impact resistance and flame retardant performance.
Abstract
Description
Technical Field
[0001] The present application relates to a thermal insulation material, and more specifically, to a ceramic coated aerogel thermal insulation pad and a preparation method thereof. Background Art
[0002] At present, aerogel insulation pads are mainly used between the cells of new energy vehicle battery packs to provide heat insulation and fire protection. In addition, silicone ceramic composite tapes, mica tapes, flame-retardant silicone strips and foam are also used in battery modules. However, in actual applications, these materials basically play a relatively single role and lack integrity, so the risk of thermal runaway is still high.
[0003] Although the existing silicone frame aerogel insulation pad can play the role of heat insulation, fire prevention and buffering, the flame retardancy of the PET film and PI film introduced in the packaging process is slightly poor and the bonding strength is reduced, resulting in poor sealing. The most fatal problem is that the aerogel has low impact strength. During long-term use, there are problems such as powder loss, reduced thermal insulation performance, and serious strength degradation and structural collapse at high temperatures. How to improve the thermal insulation, flame retardancy, resistance to combustion explosion pressure shock and insulation of the aerogel insulation pad battery pack remains to be solved. Summary of the invention
[0004] In order to solve the problem that thermal insulation materials have both thermal insulation and high temperature resistance, the present application provides a ceramic coated aerogel thermal insulation pad and a preparation method thereof.
[0005] In the first aspect, the present application provides a ceramic coated aerogel insulation pad, comprising the following raw materials in parts by mass: 40 parts of methyl acrylate, 10-15 parts of styrene, 20-25 parts of hydroxypropyl acrylate, 3-5 parts of initiator, 10-15 parts of sodium bicarbonate solution, 20-25 parts of fumed silica, 40-45 parts of ferric hydroxide sol, 30-35 parts of ceramic powder, 30-50 parts of chemically deposited ceramic fiber grafted hollow microspheres, and 10-12 parts of chopped glass fibers.
[0006] By adopting the above scheme, the components of the ceramic coating aerogel thermal insulation pad are relatively uniform, and the aerogel and gas-phase silica with excellent thermal insulation performance, the flexible chemical deposition ceramic fiber grafted hollow microspheres and the short glass fibers are relatively tightly combined together, so that the prepared thermal insulation pad has both the excellent thermal insulation performance of aerogel and the high temperature resistance of ceramics, and is not easy to collapse the structure at high temperature to cause the thermal insulation performance to fail. By adding chemical deposition ceramic fiber grafted hollow microspheres and short glass fibers, the two fibers of different lengths are interspersed with each other to improve the strength of the thermal insulation pad, and the ceramic fibers and Hollow microbeads have good thermal insulation properties. By grafting ceramic fibers with hollow microbeads, the microbeads attached to the surface of the fibers can be more tightly interlaced with other fibers. By chemically depositing the ceramic fibers grafted with hollow microbeads, a dense, high-temperature-resistant, closed-pore deposition layer is uniformly formed on the surface of the ceramic fiber grafted hollow microbeads, which combines the ceramic fibers and hollow microbeads more tightly and will not break at high temperatures. The resulting thermal insulation pad does not produce large deformation and does not lose thermal insulation properties. The formation of closed pores further reduces the thermal conductivity of the thermal insulation pad and improves the thermal insulation effect.
[0007] In a specific embodiment, the preparation steps of chemically deposited ceramic fiber grafted hollow microspheres include: placing the ceramic fiber grafted hollow microspheres in a rotary tube furnace under the protection of an inert gas, heating, introducing an active gas, keeping the temperature, and cooling to obtain chemically deposited ceramic fiber grafted hollow microspheres.
[0008] By adopting the above scheme, the chemical deposition effect is better, the preparation steps are relatively simple, more closed pores can be obtained on the surface of the ceramic fiber grafted hollow microspheres, and the connection effect between the ceramic fiber and the hollow microspheres is improved, so that the performance of the prepared thermal insulation pad is more stable at high temperatures.
[0009] In a specific embodiment, the heating rate of the deposition process is 5-7° C. / min.
[0010] By adopting the above scheme, the heating rate of the deposition process is limited, so that the surface deposition effect of the prepared chemically deposited ceramic fiber grafted hollow microbeads is better, the deposition layer formed on the surface is denser and has more closed pores, thereby greatly improving the thermal insulation and temperature resistance of the thermal insulation pad.
[0011] In a specific embodiment, the length of the ceramic fiber is 10-20 mm.
[0012] By adopting the above scheme, the length of the ceramic fiber is more appropriate, which is neither too short to limit the penetration effect in the thermal insulation pad nor too long to make it difficult for the fiber to be evenly dispersed in the system. The obtained thermal insulation pad has better performance.
[0013] In a specific embodiment, the particle size of the hollow microbeads is 700-900 nm.
[0014] By adopting the above scheme, the hollow microspheres can be better connected with the ceramic fibers, and at the same time, the particle size is smaller and the compatibility with the thermal insulation pad system is good, and debonding is not easy to occur.
[0015] In a specific embodiment, the length of the chopped glass fibers is 3-4.5 mm.
[0016] By adopting the above scheme, the chopped glass fibers can be dispersed more evenly and stably in the thermal insulation pad system, and can be well interlaced with the chemically deposited ceramic fiber grafted hollow microbeads, while not being too long so that the fibers block and entangle each other and reduce the uniformity of dispersion.
[0017] In a specific embodiment, the chopped glass fibers are silane-modified chopped glass fibers.
[0018] By adopting the above scheme, the silane-modified chopped glass fibers can be dispersed more evenly in the system and have better compatibility, further improving the structural stability of the insulation pad at high temperatures.
[0019] In a specific embodiment, the mass ratio of the chemically deposited ceramic fiber grafted hollow microspheres to the silane-modified chopped glass fibers is 4:1.
[0020] The applicant found that under the above-mentioned ratio, the thermal insulation effect and high temperature resistance of the prepared thermal insulation pad reached the best level. It may be that at this time, the chemically deposited ceramic fiber grafted hollow microbeads and silane-modified chopped glass fibers are better combined with the aerogel matrix of the thermal insulation pad, which largely retains the thermal insulation properties of the aerogel and gives the thermal insulation pad structural stability at high temperatures.
[0021] In a second aspect, the present application provides a method for preparing a ceramic coated aerogel thermal insulation pad, the preparation method comprising the following steps: S1. Evenly mix methyl acrylate, styrene, hydroxypropyl acrylate, initiator and sodium bicarbonate solution, heat, react, cool and degas to obtain a prepolymer; S2. Add the remaining components except gas-phase silica to the prepolymer, mix evenly, calender, evenly coat the surface with ceramic powder, calender, cut and seal to obtain a thermal insulation pad.
[0022] By adopting the above scheme, the preparation method is relatively simple, and the obtained thermal insulation pad is relatively uniform and stable, the components are relatively tightly connected, and the thermal insulation performance at high temperature is better.
[0023] Preferably, the ceramic powder includes one or more of calcium carbonate, silicon carbide, quartz and kaolin.
[0024] In a specific embodiment, the heating temperature is 70-80°C.
[0025] By adopting the above scheme, the prepolymerization effect is good, the components of the prepared thermal insulation pad are relatively uniform and dense, and the thermal insulation effect and high temperature resistance are good.
[0026] In summary, this application has the following beneficial effects: The present application prepares aerogel and coats and calenders a layer of ceramic powder on the surface of the aerogel, so that the prepared thermal insulation pad has both the low thermal conductivity of the aerogel and the high temperature resistance of the ceramic powder.
[0027] The present application adds a certain mass of chemically deposited ceramic fiber grafted hollow microbeads and chopped glass fibers inside the thermal insulation pad, and limits their size and mass ratio so that they are interspersed with each other to enhance the structural stability of the thermal insulation pad at high temperatures and reduce the thermal conductivity, limits the heating rate of chemical deposition to adjust the deposition effect, and further enhances the high temperature resistance of the thermal insulation pad. DETAILED DESCRIPTION
[0028] To further help understand the technical solution of the present invention, several specific embodiments are provided to describe the technical solution of the present invention in more detail. All the embodiments described are only partial embodiments of the present invention, not all of them; the embodiments can be combined with each other, and the same or similar concepts or processes may not be described in detail in some embodiments. The following embodiments are further explanations of the present invention, and the present invention is not limited thereto.
[0029] Unless otherwise specified, the experimental reagents in the preparation examples, embodiments and comparative examples in this application are all conventional commercial brands or obtained through conventional preparation processes.
[0030] Preparation Example Several specific preparation examples are provided below to more specifically describe the technical solution of the present invention, and other commonly used grafting and modification methods are also acceptable.
[0031] Preparation Example 1: Ceramic fiber grafted hollow microspheres: 45g of silane coupling agent KH-540 and 60g of ceramic fiber were added to 300g of 80wt% ethanol aqueous solution, mixed evenly, filtered, and dried to obtain modified ceramic fiber. The prepared modified ceramic fiber and 20g of hollow microspheres were added to 250ml of ethyl acetate, stirred, reacted, filtered, washed, and dried to obtain ceramic fiber grafted hollow microspheres.
[0032] In this preparation example, the average length of the ceramic fibers is 15 mm, and the average particle size of the hollow microspheres is 800 nm.
[0033] Preparation Example 2: Ceramic Fiber Grafted with Carbon Nanotubes: Add 45g of silane coupling agent KH-540 and 60g of ceramic fiber to 300g of 80wt% ethanol aqueous solution, mix evenly, filter and dry to obtain modified ceramic fiber, add the prepared modified ceramic fiber and 20g of carbon nanotubes to 250ml of ethyl acetate, stir, react, filter, wash and dry to obtain ceramic fiber grafted with carbon nanotubes.
[0034] In this preparation example, the average length of the ceramic fibers is 15 mm, and the average particle size of the carbon nanotubes is 800 nm.
[0035] Preparation Example 3: Chemically deposited ceramic fiber grafted hollow microspheres: The ceramic fiber grafted hollow microspheres prepared in Preparation Example 1 were added into a rotary tube furnace, argon was introduced, the temperature was raised to 750°C at 5°C / min, and then acetylene was introduced, and the temperature was kept for 30 minutes. The reaction was kept warm for 80 minutes and then cooled to room temperature to obtain chemically deposited ceramic fiber grafted hollow microspheres.
[0036] Preparation Example 4: Chemically deposited ceramic fibers grafted with carbon nanotubes: The ceramic fiber grafted carbon nanotubes prepared in Preparation Example 2 were added to a rotary tube furnace, argon was introduced, the temperature was raised to 750°C at 5°C / min, and then acetylene was introduced, and the temperature was kept for 30 minutes. The reaction was kept warm for 80 minutes and then cooled to room temperature to obtain chemically deposited ceramic fiber grafted carbon nanotubes.
[0037] Preparation Example 5: Silane-modified chopped glass fibers: 45 g of silane coupling agent KH-540 and 60 g of chopped glass fibers were added to 300 g of 80 wt % ethanol aqueous solution, mixed evenly, filtered, and dried to obtain silane-modified chopped glass fibers.
[0038] In this preparation example, the average particle size of the chopped glass fibers was 4 mm. Example
[0039] Example 1 In this embodiment, the thermal insulation pad includes the following raw materials by weight: 400g of methyl acrylate, 100g of styrene, 200g of hydroxypropyl acrylate, 30g of lauroyl peroxide, 100g of 20wt% sodium bicarbonate solution, 250g of fumed silica, 450g of ferric hydroxide sol, 300g of kaolin, 300g of chemically deposited ceramic fiber grafted hollow microspheres obtained in Preparation Example 3, and 120g of chopped glass fibers. The average particle size of the chopped glass fibers is 4mm.
[0040] The preparation steps are as follows: S1. Evenly mix methyl acrylate, styrene, hydroxypropyl acrylate, lauroyl peroxide and sodium bicarbonate solution, heat at 80°C, react, cool and degas to obtain a prepolymer; S2. Add the remaining components except kaolin to the prepolymer, mix evenly, calender, evenly coat the surface with ceramic powder, calender, cut and seal to obtain a thermal insulation pad.
[0041] Example 2 In this embodiment, the thermal insulation pad includes the following raw materials by weight: 400g of methyl acrylate, 150g of styrene, 200g of hydroxypropyl acrylate, 30g of lauroyl peroxide, 100g of 20wt% sodium bicarbonate solution, 200g of fumed silica, 450g of iron hydroxide sol, 350g of kaolin, 500g of chemically deposited ceramic fiber grafted hollow microspheres obtained in Preparation Example 3, and 120g of chopped glass fibers. The average particle size of the chopped glass fibers is 4mm.
[0042] The preparation steps are as follows: S1. Evenly mix methyl acrylate, styrene, hydroxypropyl acrylate, lauroyl peroxide and sodium bicarbonate solution, heat at 80°C, react, cool and degas to obtain a prepolymer; S2. Add the remaining components except kaolin to the prepolymer, mix evenly, calender, evenly coat the surface with ceramic powder, calender, cut and seal to obtain a thermal insulation pad.
[0043] Example 3 In this embodiment, the thermal insulation pad includes the following raw materials by weight: 400g of methyl acrylate, 100g of styrene, 200g of hydroxypropyl acrylate, 30g of lauroyl peroxide, 150g of 20wt% sodium bicarbonate solution, 250g of fumed silica, 450g of iron hydroxide sol, 300g of kaolin, 500g of chemically deposited ceramic fiber grafted hollow microspheres obtained in Preparation Example 3, and 120g of chopped glass fibers. The average particle size of the chopped glass fibers is 4mm.
[0044] The preparation steps are as follows: S1. Evenly mix methyl acrylate, styrene, hydroxypropyl acrylate, lauroyl peroxide and sodium bicarbonate solution, heat at 80°C, react, cool and degas to obtain a prepolymer; S2. Add the remaining components except kaolin to the prepolymer, mix evenly, calender, evenly coat the surface with ceramic powder, calender, cut and seal to obtain a thermal insulation pad.
[0045] Example 4 In this embodiment, the thermal insulation pad includes the following raw materials in parts by weight: 400g of methyl acrylate, 100g of styrene, 200g of hydroxypropyl acrylate, 30g of lauroyl peroxide, 100g of 20wt% sodium bicarbonate solution, 250g of fumed silica, 450g of iron hydroxide sol, 300g of kaolin, 300g of chemically deposited ceramic fiber grafted hollow microspheres prepared in Preparation Example 3, and 120g of silane-modified chopped glass fibers prepared in Preparation Example 5.
[0046] The preparation steps are as follows: S1. Evenly mix methyl acrylate, styrene, hydroxypropyl acrylate, lauroyl peroxide and sodium bicarbonate solution, heat at 80°C, react, cool and degas to obtain a prepolymer; S2. Add the remaining components except kaolin to the prepolymer, mix evenly, calender, evenly coat the surface with ceramic powder, calender, cut and seal to obtain a thermal insulation pad.
[0047] Example 5 In this embodiment, the thermal insulation pad includes the following raw materials in parts by weight: 400g of methyl acrylate, 100g of styrene, 200g of hydroxypropyl acrylate, 30g of lauroyl peroxide, 100g of 20wt% sodium bicarbonate solution, 250g of fumed silica, 450g of ferric hydroxide sol, 300g of kaolin, 480g of chemically deposited ceramic fiber grafted hollow microspheres prepared in Preparation Example 3, and 120g of silane-modified chopped glass fibers prepared in Preparation Example 5.
[0048] The preparation steps are as follows: S1. Evenly mix methyl acrylate, styrene, hydroxypropyl acrylate, lauroyl peroxide and sodium bicarbonate solution, heat at 80°C, react, cool and degas to obtain a prepolymer; S2. Add the remaining components except kaolin to the prepolymer, mix evenly, calender, evenly coat the surface with ceramic powder, calender, cut and seal to obtain a thermal insulation pad.
[0049] Example 6 In this embodiment, the thermal insulation pad includes the following raw materials in parts by weight: 400g of methyl acrylate, 100g of styrene, 200g of hydroxypropyl acrylate, 30g of lauroyl peroxide, 100g of 20wt% sodium bicarbonate solution, 250g of fumed silica, 450g of iron hydroxide sol, 300g of kaolin, 400g of chemically deposited ceramic fiber grafted hollow microspheres prepared in Preparation Example 3, and 100g of silane-modified chopped glass fibers prepared in Preparation Example 5.
[0050] The preparation steps are as follows: S1. Evenly mix methyl acrylate, styrene, hydroxypropyl acrylate, lauroyl peroxide and sodium bicarbonate solution, heat at 80°C, react, cool and degas to obtain a prepolymer; S2. Add the remaining components except kaolin to the prepolymer, mix evenly, calender, evenly coat the surface with ceramic powder, calender, cut and seal to obtain a thermal insulation pad.
[0051] Comparative Example Comparative Example 1 In this comparative example, the thermal insulation pad includes the following raw materials in parts by mass: 400g of methyl acrylate, 100g of styrene, 200g of hydroxypropyl acrylate, 30g of lauroyl peroxide, 100g of 20wt% sodium bicarbonate solution, 250g of fumed silica, 450g of iron hydroxide sol, 300g of kaolin, 400g of chemically deposited ceramic fiber grafted hollow microspheres prepared in Preparation Example 3, and 200g of silane-modified chopped glass fibers prepared in Preparation Example 5.
[0052] The preparation steps are as follows: S1. Evenly mix methyl acrylate, styrene, hydroxypropyl acrylate, lauroyl peroxide and sodium bicarbonate solution, heat at 80°C, react, cool and degas to obtain a prepolymer; S2. Add the remaining components except kaolin to the prepolymer, mix evenly, calender, evenly coat the surface with ceramic powder, calender, cut and seal to obtain a thermal insulation pad.
[0053] Comparative Example 2 In this comparative example, the thermal insulation pad includes the following raw materials in parts by weight: 400g of methyl acrylate, 100g of styrene, 200g of hydroxypropyl acrylate, 30g of lauroyl peroxide, 100g of 20wt% sodium bicarbonate solution, 250g of fumed silica, 450g of ferric hydroxide sol, 300g of kaolin, 300g of ceramic fiber grafted hollow microspheres obtained in Preparation Example 1, and 120g of chopped glass fibers. The average particle size of the chopped glass fibers is 4mm.
[0054] The preparation steps are as follows: S1. Evenly mix methyl acrylate, styrene, hydroxypropyl acrylate, lauroyl peroxide and sodium bicarbonate solution, heat at 80°C, react, cool and degas to obtain a prepolymer; S2. Add the remaining components except kaolin to the prepolymer, mix evenly, calender, evenly coat the surface with ceramic powder, calender, cut and seal to obtain a thermal insulation pad.
[0055] Comparative Example 3 In this comparative example, the thermal insulation pad includes the following raw materials in parts by weight: 400g of methyl acrylate, 100g of styrene, 200g of hydroxypropyl acrylate, 30g of lauroyl peroxide, 100g of 20wt% sodium bicarbonate solution, 250g of fumed silica, 450g of iron hydroxide sol, 300g of kaolin, 300g of chemically deposited ceramic fiber grafted carbon nanotubes obtained in Preparation Example 4, and 120g of chopped glass fibers. The average particle size of the chopped glass fibers is 4mm.
[0056] The preparation steps are as follows: S1. Evenly mix methyl acrylate, styrene, hydroxypropyl acrylate, lauroyl peroxide and sodium bicarbonate solution, heat at 80°C, react, cool and degas to obtain a prepolymer; S2. Add the remaining components except kaolin to the prepolymer, mix evenly, calender, evenly coat the surface with ceramic powder, calender, cut and seal to obtain a thermal insulation pad.
[0057] Performance test test 1: Referring to the standard: GB / T10294-2008 Determination of steady-state thermal resistance and related properties of insulation materials, the method described in the protective hot plate method was used to test the thermal conductivity 1 of the insulation pads prepared by the embodiments and comparative examples at 25°C, and the test results are summarized in Table 1; Test 2: The absorbing materials prepared by the embodiments and comparative examples were placed at 500°C for 30 minutes, and the thermal conductivity 2 was tested. The thermal conductivity retention rate (%) was calculated according to the thermal conductivity 1 / thermal conductivity 2×100%, and the test results are summarized in Table 1.
[0058] Table 1 Thermal conductivity 1 (W / m×K) Thermal conductivity retention (%) Example 1 0.0041 92 Example 2 0.0039 93 Example 3 0.0042 92 Example 4 0.0033 95 Example 5 0.0030 98 Example 6 0.0031 98 Comparative Example 1 0.0044 91 Comparative Example 2 0.0047 87 Comparative Example 3 0.0052 81 This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A ceramic coated aerogel thermal insulation pad, Features: The thermal insulation pad comprises the following raw materials in parts by mass: 40 parts of methyl acrylate, 10-15 parts of styrene, 20-25 parts of hydroxypropyl acrylate, 3-5 parts of initiator, 10-15 parts of sodium bicarbonate solution, 20-25 parts of fumed silica, 40-45 parts of ferric hydroxide sol, 30-35 parts of ceramic powder, 30-50 parts of chemically deposited ceramic fiber grafted hollow microspheres, and 10-12 parts of chopped glass fibers.
2. A ceramic coating aerogel thermal insulation pad according to claim 1, Features: The preparation steps of the chemically deposited ceramic fiber grafted hollow microspheres include: placing the ceramic fiber grafted hollow microspheres in a rotary tube furnace under the protection of inert gas, heating up, introducing active gas, keeping the temperature, and cooling down to obtain the chemically deposited ceramic fiber grafted hollow microspheres.
3. A ceramic coating aerogel thermal insulation pad according to claim 2, Features: The heating rate of the deposition process is 5-7°C / min.
4. The ceramic-coated aerogel thermal insulation pad according to claim 2, Features: The length of the ceramic fiber is 10-20 mm.
5. The ceramic-coated aerogel thermal insulation pad according to claim 2, Features: The particle size of the hollow microbeads is 700-900nm.
6. The ceramic-coated aerogel thermal insulation pad according to claim 4, Features: The length of the chopped glass fibers is 3-4.5 mm.
7. The ceramic-coated aerogel thermal insulation pad according to claim 4, Features: The chopped glass fibers are silane-modified chopped glass fibers.
8. The ceramic-coated aerogel thermal insulation pad according to claim 7, Features: The mass ratio of the chemically deposited ceramic fiber grafted hollow microspheres to the silane-modified chopped glass fibers is 4:
1.
9. A method for preparing a ceramic coating aerogel thermal insulation pad according to any one of claims 1 to 8, Features: The preparation method comprises the following steps: S1. Evenly mix methyl acrylate, styrene, hydroxypropyl acrylate, initiator and sodium bicarbonate solution, heat, react, cool and degas to obtain a prepolymer; S2. Add the remaining components except ceramic powder to the prepolymer, mix evenly, calender, evenly coat the surface with ceramic powder, calender, cut and seal to obtain a thermal insulation pad.
10. A method for preparing a ceramic coating aerogel thermal insulation pad according to claim 9, Features: The heating temperature is 70-80°C.
